1991
DOI: 10.1002/ana.410290316
|View full text |Cite
|
Sign up to set email alerts
|

A selective loss of somatostatin in the hippocampus of patients with temporal lobe epilepsy

Abstract: Although neuropeptides have been demonstrated to be hippocampal neuromodulators in laboratory animals, their role in human hippocampal physiology or pathophysiology remains to be defined. The concentrations of somatostatin, cholecystokinin octapeptide, vasoactive intestinal polypeptide, and dynorphin A 1-17 were determined in hippocampal tissue resected from patients with cryptogenic temporal lobe epilepsy, a common seizure disorder originating in or near the hippocampus. Control tissue was obtained from cadav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
0
3

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(95 citation statements)
references
References 51 publications
6
86
0
3
Order By: Relevance
“…Double labeling for somatostatin revealed that STEP was enriched in somatostatinergic hilar interneurons. As noted above, this subclass of interneurons is highly vulnerable to SE-induced excitotoxicity (Robbins et al, 1991;Buckmaster and Jongen-Rélo, 1999). We found that acute SE-induced cell death was correlated with STEP expression in the hilus.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Double labeling for somatostatin revealed that STEP was enriched in somatostatinergic hilar interneurons. As noted above, this subclass of interneurons is highly vulnerable to SE-induced excitotoxicity (Robbins et al, 1991;Buckmaster and Jongen-Rélo, 1999). We found that acute SE-induced cell death was correlated with STEP expression in the hilus.…”
Section: Discussionsupporting
confidence: 78%
“…Of note is the marked decrease in somatostatin-positive interneurons both in patients with TLE (de Lanerolle et al, 1989;Robbins et al, 1991) and in animal models of TLE (Sloviter, 1987;Sloviter, 1991;Buckmaster and Dudek, 1997;Buckmaster and Jongen-Rélo, 1999). For example, postmortem analysis has revealed that the number of somatostatin-positive neurons is reduced by 80% in individuals with TLE (Robbins et al, 1991), and, in the kainic acid model of TLE, somatostatin-positive hilar interneurons account for Ͼ80% of the GABAergic cells that were lost (Buckmaster and JongenRélo, 1999). Given these observations, insight into the molecular mechanism responsible for the subclass-specific vulnerability of interneurons to SE-induced cell death may provide a deeper understanding of temporal lobe epileptogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Shortly thereafter, this specific pattern of neuron loss was confirmed in humans with temporal lobe epilepsy (de Lanerolle et al, 1989), and an upregulation of SST binding sites in human tissue was also noted (Robbins et al, 1991). Since these first reports, the loss of SST-containing hilar interneurons has been observed in many animal models, including kainate Sperk et al, 1992) and pilocarpine (Choi et al, 2007;Kobayashi and Buckmaster, 2003), and is now considered a hallmark of epileptic hippocampus.…”
Section: Seizures Induce the Loss Of Sst-containing Interneurons In Tmentioning
confidence: 87%
“…So far, the anatomical and physiological basis for disinhibition of hippocampal pathways is not fully understood. Loss of other interneuronal subpopulations, such as somatostatin-and neuropeptide Y-containing interneurons (34)(35)(36), as well as of parvalbumin-immunoreactive inhibitory basket cells (37) in the hilus of human epilepsy specimens, could also play a role.…”
Section: Fig 3 Hilar Mossy Cells In the Human Hippocampusmentioning
confidence: 99%